1996
DOI: 10.1175/1520-0477(1996)077<1497:iartth>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Impacts and Responses to the 1995 Heat Wave: A Call to Action

Abstract: The short but intense heat wave in mid-July 1995 caused 830 deaths nationally, with 525 of these deaths in Chicago. Many of the dead were elderly, and the event raised great concern over why it happened. Assessment of causes for the heat wave-related deaths in Chicago revealed many factors were at fault, including an inadequate local heat wave warning system, power failures, questionable death assessments, inadequate ambulance service and hospital facilities, the heat island, an aging population, and the inabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
164
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(166 citation statements)
references
References 2 publications
0
164
0
2
Order By: Relevance
“…Thus, surface UHI and its associated data source, LST, have been increasingly used in the study of urban climate in recent decades (EPA, 2009;Mirzaei and Haghighat, 2010). Previous studies have shown that both air and surface UHIs are associated with heat waves (Changnon et al, 1996;Fischer et al, 2007), disease (Liu and Weng, 2009) and pose a health risk to more than 50% of the world's population (Frumkin and McMichael, 2008;Wu, 2010). Hence, sustainable urbanization is urgently needed to mitigate the effects of UHIs and improve urban living conditions (Opdam et al, 2009;Wu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, surface UHI and its associated data source, LST, have been increasingly used in the study of urban climate in recent decades (EPA, 2009;Mirzaei and Haghighat, 2010). Previous studies have shown that both air and surface UHIs are associated with heat waves (Changnon et al, 1996;Fischer et al, 2007), disease (Liu and Weng, 2009) and pose a health risk to more than 50% of the world's population (Frumkin and McMichael, 2008;Wu, 2010). Hence, sustainable urbanization is urgently needed to mitigate the effects of UHIs and improve urban living conditions (Opdam et al, 2009;Wu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Heat is the deadliest of all atmospheric phenomena (Changnon et al, 1996;Sheridan and Kalkstein, 2004). Heat-related mortality can be defined as the incidence of deaths which would not occur in the absence of heat stress (Zaninović and Matzarakis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Extreme events have had tremendous impact on the United States in recent years, including insured property losses in excess of $5 billion per year during the 1990s (14). Three events, the midwest drought in 1988-1989, Hurricane Andrew in 1992, and the midwest flood in 1993, accounted for $88 billion in total losses (14), and heat-waves in the summer of 1995 claimed 1,100 lives (14), including 525 in Chicago during a single 3-week period (15). In addition to these recent catastrophes, the late 20th century has exhibited positive trends in frequency of hot events (16) and heavy precipitation events (17,18), and negative trends in frequency of cold events (16,19).…”
mentioning
confidence: 99%